UPAYA MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYYAH ANAK USIA DINI MELALUI KARTU BERWARNA DI TK HARAPAN BANGSA TLOGOWUNGU PATI - Husnul hafidhoh; Mazidah, Nihayatul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2023)
The ability to read hijaiyah letters is an important improvement for an early age as a provision for the future. It is a must to learn hijaiyah letters as a Muslim child as applied and accustomed to learning as early as possible. As the times progressed, many influences, one of which came from bad habits, resulted in the effect of parents being more extravagant and setting an example. Parents entrust early childhood education supporters to teachers so that they are more familiar with and improve their reading of the hijaiyah letters. This study aims to find out the role of hijaiyah letter cards through colored cards in improving the cognitive and language aspects of early childhood in the ability to read hijaiyah letters, the ability to remember letters sequentially and randomly, recognize colors in Harapan Bangsa Kindergarten Tlogowungu Pati. The research was conducted in HARAPAN BANGSA Kindergarten Group B Cabak Tlogowungu with a total of 20 children. The results of this study after showing that the action through colored cards that appear hijaiyyah letters in children's cognitive and language development increases and develops well. At the time of pre-cycle observation, the percentage of development was 32.2%, then it increased in the implementation of the week of 44.53% and in the second week of implementation there was a very good increase of u83.54. The steps achieved so that the child's cognitive and language development increases: pre-development activities, development activities, and closing activities. Guidance is given during development activities and at closing.